The Cultural Dynamics of Democratization in Spain - McDonough, Peter, 1939- (Book collections on Project MUSE., 1998)
Since the death of Franco in 1975, Spain has made a successful transition to democracy. This book looks at what that transition has meant for the Spanish people. Drawing on national surveys taken in 1978, 1980, 1984, and 1990, the authors explore three questions: What is the basis of the new regime's political legitimacy? How did Spanish democracy move from the conservative center-right coalition that engineered the transition to the socialist government that consolidated it? And why is political participation so low among Spaniards?